2019
DOI: 10.1098/rsfs.2019.0038
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of degeneracy in the genetic code

Abstract: The degeneracy of amino acid coding is one of the most crucial and enigmatic aspects of the genetic code. Different theories about the origin of the genetic code have been developed. However, to date, there is no comprehensive hypothesis on the mechanism that might have generated the degeneracy as we observe it. Here, we provide a new theory that explains the origin of the degeneracy based only on symmetry principles. The approach allows one to describe exactly the degeneracy of the early code (progenitor of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…In this work we have identified and characterized circular tessera codes and their properties. In Gonzalez et al (2012) and Gonzalez et al (2019) Gonzalez, Giannerini and Rosa had proposed an ancestor code of the universal genetic code that is based on 64 tetranucleotides built from dinucleotides by using the Klein four symmetry group. It was hypothesized that this tessera code existed before LUCA and even before the early genetic code that coded for 20 amino acids using all 64 codons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work we have identified and characterized circular tessera codes and their properties. In Gonzalez et al (2012) and Gonzalez et al (2019) Gonzalez, Giannerini and Rosa had proposed an ancestor code of the universal genetic code that is based on 64 tetranucleotides built from dinucleotides by using the Klein four symmetry group. It was hypothesized that this tessera code existed before LUCA and even before the early genetic code that coded for 20 amino acids using all 64 codons.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that during evolution the genetic code had several ancestors that might have consisted not only of trinucleotides but of dinucleotides or tetranucleotides or even combinations of these (see Baranov et al 2009;Gonzalez et al 2012;Seligmann 2014;Patel 2005;Wilhelm and Nikolajewa 2004;Wu et al 2005). In particular, in Gonzalez et al (2012) the tessera code was suggested as an ancestral code that might have been the origin of the mitochondrial code (see also Gonzalez et al 2019). In order to define the tessera code we have to introduce some group theory and how it can be applied in the genetic setting.…”
Section: Definitions and Notationsmentioning
confidence: 99%
See 3 more Smart Citations